2019
DOI: 10.1021/acs.cgd.9b00664
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Hydrogen-Bonded Assemblies of Twisted Tetra[3,4]thienylene Tetracarboxylic Acid with Selective Solvent Sorption

Abstract: We demonstrated versatile hydrogen-bonded assemblies of a twisted π system with newly synthesized tetra­[3,4]­thienylene tetracarboxylic acid ThTCA. Due to its twisted saddle-shaped central π aromatic unit with an anisotropic arrangement of carboxyl units, a variety of dimensional solvate molecular crystals could be obtained, in contrast to typical aromatic carboxylic acid derivatives with low-dimensional assemblies. The versatile molecular assemblies could be converged to ThTCA desol by desolvation with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A slight modification of ligands, change of solvents, or reaction temperature may significantly alter the self-assembled products. [15][16][17] As a result, many attempted syntheses of HOFs in a one-pot reaction may end up with non-porous products formed by closely packed ligands. For comparison, metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), with coordination bonds and covalent bonds, can be rationally designed and synthesized based on reticular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…A slight modification of ligands, change of solvents, or reaction temperature may significantly alter the self-assembled products. [15][16][17] As a result, many attempted syntheses of HOFs in a one-pot reaction may end up with non-porous products formed by closely packed ligands. For comparison, metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), with coordination bonds and covalent bonds, can be rationally designed and synthesized based on reticular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high crystallinity, easy recrystallization process to obtain, and developing design strategy based on multiplicity and/or directionality of hydrogen bonds, various HOFs have been constructed and investigated their properties as a new class of porous frameworks. [29][30][31][32][33][34][35] In connection with HOFs, we previously demonstrated that C3-symmetric πconjugated hydrocarbons, such as a triphenylene derivative Tp, possessing six carboxyphenyl groups in their periphery (Chart 1) form hydrogen-bonded hexagonal network (H-HexNet) and that the H-HexNet stacks without interpenetration to yield the corresponding layered HOFs. [36][37][38] More recently, Chen and coworkers report a HOF based on C3-or C6-symmetric benzene derivatives with carboxy groups.…”
Section: Introductionmentioning
confidence: 99%
“…HOFs are porous molecular crystals particularly constructed through intermolecular hydrogen bonds. Because of their high crystallinity, easy recrystallization process, and development of a design strategy based on multiplicity and/or directionality of hydrogen bonds, various HOFs have been constructed and their properties investigated as a new class of porous frameworks. In connection with HOFs, we previously demonstrated that C 3 -symmetric π-conjugated hydrocarbons, such as the triphenylene derivative Tp , possessing six carboxyphenyl groups in its periphery (Chart ), form a hydrogen-bonded hexagonal network (H-HexNet) and that the H-HexNet stacks without interpenetration to yield the corresponding layered HOFs. More recently, Chen and co-workers reported a HOF based on C 3 - or C 6 -symmetric benzene derivatives with carboxy groups. , Interestingly, when the triphenylene moiety of Tp was replaced by hexaazatriphenylene (HAT), the resulting derivative CPHAT did not form a layered 2D framework but rather a three-dimensional (3D) rigid framework with permanent porosity. , In the 3D framework, the HAT moiety is deformed into a propeller-shaped conformation by packing forces. Because of the conformation, the six peripheral carboxyphenyl groups alternately project upward and downward to form a 3D H-bonded network.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in solids, the Na + cations and Cl – anions are tightly bonded due to the strong electrostatic interaction between the charged ions; this drastically suppresses ionic mobility. The hybridization of ionic and covalent bonds form a rigid three-dimensional (3D) crystal lattice in inorganic crystals, while a variety of intermolecular interactions such as electrostatic, charger-transfer, hydrogen-bonding, and van der Waals interactions play an essential role in determining the crystal lattice and enhancing the variation of the structural dimension in the molecular crystals. Therefore, the chemical design of a variety of crystal lattices is conventionally possible to ensure a suitable H + -conducting pathway for achieving a high μ H+ value in the molecular crystal where the freedom of motion of H + in the crystal lattice can be thermally activated even at a relatively low temperature. , …”
Section: Introductionmentioning
confidence: 99%